Boron nitride nanosheet-aramid nanofiber composite film and preparation method thereof

Calcium ionic sodium alginate auxiliary ball grinding and peeling and thermal composite composite technology, prepare high -vertical composite BNNS and aramite nano -fiber composite film, solve the problem of low thermal conductivity of BNNS in the existing technology, and achieve high thermal guidance. Rate composite material.

CN119331282AActive Publication Date: 2025-01-21SHAANXI UNIV OF SCI & TECH

Patent Information

Application Number
CN202411343554.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-01-21
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

It is difficult to prepare boron nitride nanosheets (BNNS) with large and single layers, resulting in low thermal conductivity of the material and affecting the stability and reliability of electronic components.

Method used

The calcium ionic sodium alginate is assisted and stripped out, and the high vertical and horizontal ratio of the high and smaller thickness is prepared to effectively compound the aramn nano fiber with the BNNS through the thermal pressure method to build a continuous thermal network in the surface.

Benefits of technology

The thermal conductivity of the composite film is increased to 23.86-27.57W·m-1·K-1, which meets the needs of high thermal conductivity areas and improves the interface density and contact area of ​​the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331282A_ABST
    Figure CN119331282A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of composite film materials, and particularly relates to a boron nitride nanosheet-aramid nanofiber composite film and a preparation method thereof.The preparation method comprises the steps that calcium chloride is dissolved in a sodium alginate aqueous solution, and a Ca < 2 + > / SA cross-linking solution is obtained; adding hexagonal boron nitride into the Ca < 2 + > / SA cross-linking solution, and magnetically stirring to realize pre-infiltration so as to obtain a pre-infiltrated SA / BNNS solution; carrying out ball milling and washing on the pre-infiltrated SA / BNNS solution to obtain a BNNS / water suspension; mixing the BNNS / water suspension with the ANF / DMSO dispersion liquid to obtain a BNNS / ANF mixed solution; carrying out vacuum filtration, drying and hot pressing treatment on the BNNS / ANF mixed solution to obtain a boron nitride nanosheet-aramid nanofiber composite film; by improving interface phonon scattering between BNNS, the interface density of the material is lower, the contact area of the interface is larger, and therefore the heat conductivity of the composite film is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite film materials, and particularly relates to a boron nitride nanosheet-aramid nanofiber composite film and a preparation method thereof. Background Art

[0002] In recent years, with the rapid development of microelectronics technology and integrated circuits, electronic devices are increasingly tending towards high integration, high power and multifunctionality. However, this is followed by a serious heating problem of electronic devices; on the one hand, due to the extensive application of integrated circuits and microelectronic components, the size of the equipment has been reduced by thousands of times, greatly improving the portability and popularity of the equipment, but at the same time it has also caused serious heat accumulation; on the other hand, the continuous increase in operating power has also greatly increased the heat generated during operation, resulting in higher and higher operating temperatures of electronic components; the accumulation of heat in the equipment will not only affect the stability and reliability of electronic components, but also cause a series of problems such as aging and failure of materials, thereby affecting the stable operation of the entire electronic equipment and shortening the operating life of the equipment; therefore, the thermal management of electronic devices is a key factor in ensuring the normal operation of electronic equipment, and it is urgent to explore thermal management materials with excellent comprehensive performance.

[0003] Polymer-based high thermal conductivity composite materials are currently one of the mainstream research directions for improving thermal management efficiency, but how to maximize the intrinsic high thermal conductivity advantage of fillers needs further exploration; hexagonal boron nitride (h-BN) is a graphene-like layered material with thick flakes and smooth surface, so it is difficult to stack tightly and has poor wettability and dispersibility with polymers; therefore, h-BN is usually exfoliated into boron nitride nanosheets (BNNS) or functionalized with organic matter, and then filled into polymers to construct thermal conductive composite materials; however, the existing exfoliation methods make it difficult to prepare large and single-layer BNNS, which leads to low thermal conductivity of the material, which seriously affects the stability and reliability of electronic components. Summary of the invention

[0004] In view of the technical problems existing in the prior art, the present invention provides a boron nitride nanosheet-aramid nanofiber composite film and a preparation method thereof, so as to solve the technical problem that the existing peeling method is difficult to prepare large and single-layer BNNS, which leads to low thermal conductivity of the material.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is: The present invention provides a method for preparing a boron nitride nanosheet-aramid nanofiber composite film, comprising: Dissolve calcium chloride in sodium alginate aqueous solution to obtain Ca 2+ / SA cross-linking solution; Adding hexagonal boron nitride to Ca2+ / SA cross-linking solution, pre-wetting by magnetic stirring to obtain a pre-wetted SA / BNNS solution; ball milling and washing the pre-wetted SA / BNNS solution to obtain a BNNS / water suspension; Mixing the BNNS / water suspension with the ANF / DMSO dispersion to obtain a BNNS / ANF mixed solution; The BNNS / ANF mixed solution was vacuum filtered, dried and hot pressed to obtain a boron nitride nanosheet-aramid nanofiber composite film.

[0006] Furthermore, Ca 2+ Ca / SA cross-linking solution 2+ The concentration is 1-4mmol / L.

[0007] Furthermore, the pre-impregnated SA / BNNS solution was ball-milled and washed to obtain a BNNS / water suspension, and the ball-milling time was 12-24 h.

[0008] Furthermore, the pre-soaked SA / BNNS solution was ball-milled and washed to obtain a BNNS / water suspension, which was washed with deionized water.

[0009] Further, the concentration of the BNNS / water suspension is 5-10 mg / mL.

[0010] Further, the preparation process of ANF / DMSO dispersion is as follows: The para-PPTA fibers and potassium hydroxide were dispersed in DMSO and stirred continuously to obtain an ANF / DMSO dispersion.

[0011] Furthermore, the concentration of the ANF / DMSO dispersion is 1-5 mg / mL.

[0012] Furthermore, the preparation process of the sodium alginate aqueous solution is specifically as follows: Sodium alginate is added into deionized water, and stirred to dissolve to obtain a sodium alginate aqueous solution.

[0013] The present invention also provides a boron nitride nanosheet-aramid nanofiber composite film, which is prepared by using the preparation method of the boron nitride nanosheet-aramid nanofiber composite film.

[0014] Furthermore, the thermal conductivity of the boron nitride nanosheet-aramid nanofiber composite film is 23.86-27.57 W·m -1 ·K -1 .

[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a boron nitride nanosheet-aramid nanofiber composite film and a preparation method thereof. ANF is used as a polymer substrate and BNNS is used as a thermal conductive filler. The boron nitride nanosheet-aramid nanofiber composite film is prepared by vacuum filtration and hot pressing. The calcium ion cross-linked sodium alginate is assisted by ball milling to obtain a high aspect ratio BNNS with a large lateral size and a small thickness, thereby improving the interface phonon scattering between the BNNS, making the interface density of the composite material lower and the contact area of ​​the interface larger, thereby improving the thermal conductivity of the composite film. Secondly, the ANF and BNNS are effectively compounded by hot pressing, and the BNNS is oriented in-plane to construct a continuous thermal conductive network in the plane, so that the composite material has good thermal conductivity and can be applied to fields with high thermal conductivity requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0017] Figure 1 is the SEM image of BNNS after ball milling in the comparative example; Figure 2 SEM image of BNNS after ball milling in Example 5 Figure 3 TEM image of BNNS after ball milling in Example 5; Figure 4 Graphs showing the thermal conductivity of the boron nitride nanosheet-aramid nanofiber composite films prepared in Examples 3-5 and Comparative Examples. DETAILED DESCRIPTION

[0018] In order to make the technical problems, technical solutions and beneficial effects solved by this application clearer, the technical solutions in the embodiments of this application will be described clearly and completely in combination with the drawings in the embodiments of this application; obviously, the described embodiments are only part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0019] The present invention provides a method for preparing a boron nitride nanosheet-aramid nanofiber composite film, comprising the following steps: Step 1: Add sodium alginate (SA) into deionized water, stir and dissolve to obtain a SA aqueous solution with a concentration of 1-2 wt%.

[0020] Step 2: Dissolve calcium chloride (CaCl2) in SA aqueous solution to obtain Ca 2+ Ca concentration of 1-4 mmol / L 2+ / SA cross-linking solution.

[0021] Step 3: Add hexagonal boron nitride (h-BN) to Ca 2+ / SA solution to obtain a mixed solution; wherein the concentration of h-BN in the mixed solution is 40-60 mg / mL, and magnetic stirring is performed for 36-60 hours to achieve pre-infiltration to obtain a pre-infiltrated SA / BNNS solution.

[0022] Step 4: Measure 10-30 mL of the pre-soaked SA / BNNS solution, ball-mill at 300-400 rpm for 12-24 h, then wash with deionized water for 3-5 times, and dilute with deionized water after washing to obtain a BNNS / water suspension; wherein the concentration of BNNS in the BNNS / water suspension is 5-10 mg / mL.

[0023] Step 5: Mix the para-PPTA fiber and KOH and disperse them in DMSO, and continue stirring to obtain an ANF / DMSO dispersion with a concentration of 1-5 mg / mL.

[0024] Step 6: Mix the BNNS / water suspension with the ANF / DMSO dispersion to obtain a BNNS / ANF mixed solution.

[0025] Step 7: The BNNS / ANF mixed solution is vacuum filtered, dried, and hot pressed to obtain a boron nitride nanosheet-aramid nanofiber composite film.

[0026] Preparation principle: The method for preparing the boron nitride nanosheet-aramid nanofiber composite film of the present invention comprises the following steps: selecting an SA aqueous solution according to the viscosity to ball-mill and peel off h-BN, and further introducing Ca 2+ The SA chains are cross-linked to enhance their interfacial interaction with h-BN, aiming to increase the lateral size and thin layer of the prepared BNNSs to a greater extent; ANF and BNNS are effectively compounded by hot pressing, and the BNNS are oriented in-plane to construct a continuous in-plane thermal conductive network, so that the composite material has good thermal conductivity; among them, ANF has excellent mechanical reinforcement properties, thermal stability, insulation and good processability, and is used as a mechanical reinforcement phase of the polymer matrix; the prepared BNNS with large lateral size and thin thickness has high intrinsic thermal conductivity, electrical insulation, chemical stability and thermal stability. The addition of BNNS can not only effectively enhance the thermal conductivity of the polymer matrix, but also significantly enhance the breakdown strength of the material, reduce dielectric loss, and obtain a polymer-based composite material with excellent insulation properties.

[0027] Example 1 This embodiment 1 provides a method for preparing a boron nitride nanosheet-aramid nanofiber composite film, comprising the following steps: Step 1: Add sodium alginate (SA) into deionized water, stir and dissolve to obtain a 1 wt% SA aqueous solution.

[0028] Step 2: Dissolve calcium chloride (CaCl2) in SA aqueous solution to obtain a Ca solution with a concentration of 1 mmol / L. 2+ / SA cross-linking solution.

[0029] Step 3: Add hexagonal boron nitride (h-BN) to Ca 2+ / SA solution to obtain a mixed solution; wherein the concentration of h-BN in the mixed solution is 40 mg / mL, and magnetic stirring is performed for 36 hours to achieve pre-infiltration to obtain a pre-infiltrated SA / BNNS solution.

[0030] Step 4: Measure 10 mL of the pre-soaked SA / BNNS solution, ball-mill at 300 rpm for 12 h, then wash with deionized water three times, and dilute with deionized water after washing to obtain a BNNS / water suspension; wherein the concentration of BNNS in the BNNS / water suspension is 5 mg / mL.

[0031] Step 5: Mix the para-PPTA fiber and KOH and disperse them in DMSO, and continue stirring to obtain an ANF / DMSO dispersion with a concentration of 1 mg / mL.

[0032] Step 6: Mix the BNNS / water suspension with the ANF / DMSO dispersion to obtain a BNNS / ANF mixed solution.

[0033] Step 7: The BNNS / ANF mixed solution is vacuum filtered, dried, and hot pressed to obtain a boron nitride nanosheet-aramid nanofiber composite film.

[0034] Example 2 This embodiment 2 provides a method for preparing a boron nitride nanosheet-aramid nanofiber composite film, comprising the following steps: Step 1: Add sodium alginate (SA) into deionized water, stir and dissolve to obtain a 2 wt% SA aqueous solution.

[0035] Step 2: Dissolve calcium chloride (CaCl2) in SA aqueous solution to obtain a Ca solution with a concentration of 4 mmol / L. 2+ / SA cross-linking solution.

[0036] Step 3: Add hexagonal boron nitride (h-BN) to Ca 2+ / SA solution to obtain a mixed solution; wherein the concentration of h-BN in the mixed solution is 60 mg / mL, and magnetic stirring is performed for 60 hours to achieve pre-infiltration to obtain a pre-infiltrated SA / BNNS solution.

[0037] Step 4: Measure 30 mL of the pre-soaked SA / BNNS solution, ball-mill at 400 rpm for 24 h, then wash with deionized water 5 times, and dilute with deionized water after washing to obtain a BNNS / water suspension; wherein the concentration of BNNS in the BNNS / water suspension is 10 mg / mL.

[0038] Step 5: Mix the para-PPTA fiber and KOH and disperse them in DMSO, and continue stirring to obtain an ANF / DMSO dispersion with a concentration of 5 mg / mL.

[0039] Step 6: Mix the BNNS / water suspension with the ANF / DMSO dispersion to obtain a BNNS / ANF mixed solution.

[0040] Step 7: The BNNS / ANF mixed solution is vacuum filtered, dried, and hot pressed to obtain a boron nitride nanosheet-aramid nanofiber composite film.

[0041] Example 3 This embodiment 3 provides a method for preparing a boron nitride nanosheet-aramid nanofiber composite film, comprising the following steps: Step 1: Add sodium alginate (SA) into deionized water, stir and dissolve to obtain a SA aqueous solution with a concentration of 1.5 wt%.

[0042] Step 2: Dissolve calcium chloride (CaCl2) in SA aqueous solution to obtain a Ca solution with a concentration of 1 mmol / L. 2+ / SA cross-linking solution.

[0043] Step 3: Add hexagonal boron nitride (h-BN) to Ca 2+ / SA solution to obtain a mixed solution; wherein the concentration of h-BN in the mixed solution is 50 mg / mL, and magnetic stirring is performed for 48 hours to achieve pre-infiltration to obtain a pre-infiltrated SA / BNNS solution.

[0044] Step 4: Measure 20 mL of the pre-soaked SA / BNNS solution, ball-mill at 350 rpm for 18 h, then wash with deionized water 4 times, and dilute with deionized water after washing to obtain a BNNS / water suspension; wherein the concentration of BNNS in the BNNS / water suspension is 7 mg / mL.

[0045] Step 5: Mix the para-PPTA fiber and KOH and disperse them in DMSO, and continue stirring to obtain an ANF / DMSO dispersion with a concentration of 3 mg / mL.

[0046] Step 6: Mix the BNNS / water suspension with the ANF / DMSO dispersion to obtain a BNNS / ANF mixed solution.

[0047] Step 7: The BNNS / ANF mixed solution is vacuum filtered, dried, and hot pressed to obtain a boron nitride nanosheet-aramid nanofiber composite film.

[0048] Example 4 This embodiment 4 provides a method for preparing a boron nitride nanosheet-aramid nanofiber composite film, comprising the following steps: Step 1: Add sodium alginate (SA) into deionized water, stir and dissolve to obtain a SA aqueous solution with a concentration of 1.2 wt%.

[0049] Step 2: Dissolve calcium chloride (CaCl2) in SA aqueous solution to obtain a Ca solution with a concentration of 2 mmol / L. 2+ / SA cross-linking solution.

[0050] Step 3: Add hexagonal boron nitride (h-BN) to Ca 2+ / SA solution to obtain a mixed solution; wherein the concentration of h-BN in the mixed solution is 50 mg / mL, and magnetic stirring is performed for 48 hours to achieve pre-infiltration to obtain a pre-infiltrated SA / BNNS solution.

[0051] Step 4: Measure 10 mL of the pre-soaked SA / BNNS solution, ball-mill at 400 rpm for 24 h, then wash with deionized water 4 times, and dilute with deionized water after washing to obtain a BNNS / water suspension; wherein the concentration of BNNS in the BNNS / water suspension is 8 mg / mL.

[0052] Step 5: Mix the para-PPTA fiber and KOH and disperse them in DMSO, and continue stirring to obtain an ANF / DMSO dispersion with a concentration of 4 mg / mL.

[0053] Step 6: Mix the BNNS / water suspension with the ANF / DMSO dispersion to obtain a BNNS / ANF mixed solution.

[0054] Step 7: The BNNS / ANF mixed solution is vacuum filtered, dried, and hot pressed to obtain a boron nitride nanosheet-aramid nanofiber composite film.

[0055] Example 5 This embodiment 5 provides a method for preparing a boron nitride nanosheet-aramid nanofiber composite film, comprising the following steps: Step 1: Add sodium alginate (SA) into deionized water, stir and dissolve to obtain a 1 wt% SA aqueous solution.

[0056] Step 2: Dissolve calcium chloride (CaCl2) in SA aqueous solution to obtain a Ca solution with a concentration of 4 mmol / L. 2+ / SA cross-linking solution.

[0057] Step 3: Add hexagonal boron nitride (h-BN) to Ca 2+ / SA solution to obtain a mixed solution; wherein the concentration of h-BN in the mixed solution is 50 mg / mL, and magnetic stirring is performed for 48 hours to achieve pre-infiltration to obtain a pre-infiltrated SA / BNNS solution.

[0058] Step 4: Measure 10 mL of the pre-soaked SA / BNNS solution, ball-mill at 400 rpm for 24 h, then wash with deionized water 4 times, and dilute with deionized water after washing to obtain a BNNS / water suspension; wherein the concentration of BNNS in the BNNS / water suspension is 7 mg / mL.

[0059] Step 5: Mix the para-PPTA fiber and KOH and disperse them in DMSO, and continue stirring to obtain an ANF / DMSO dispersion with a concentration of 2.5 mg / mL.

[0060] Step 6: Mix the BNNS / water suspension with the ANF / DMSO dispersion to obtain a BNNS / ANF mixed solution.

[0061] Step 7: The BNNS / ANF mixed solution is vacuum filtered, dried, and hot pressed to obtain a boron nitride nanosheet-aramid nanofiber composite film.

[0062] Comparative Example The process and principle of this comparative example are basically the same as those of the above-mentioned embodiment 5, except that: The amount of calcium chloride added in step 2 of Example 5 was adjusted to 0, that is, no calcium chloride was added in this comparative example; the remaining steps were basically the same and will not be repeated here.

[0063] As attached Figure 1-2 As shown, attached Figure 1 The SEM images of the BNNS after ball milling in the comparative example are given in Figure 2 The SEM images of the BNNS after ball milling in Example 5 are given in FIG. Figure 1-2 As can be seen, the introduction of Ca 2+ The lateral size of BNNSs was significantly increased after exfoliation, and the thickness of the finished product prepared by exfoliation was thin, and the curling of the nanosheets could be observed. This is due to the fact that Ca 2+ The cross-linking degree of SA is promoted and the resistance of the h-BN layer to impact force is enhanced.

[0064] As attached Figure 3 As shown, attached Figure 3The TEM image of the BNNS after ball milling in Example 5 is given in FIG. , which also shows that the BNNS prepared by exfoliation has the characteristics of large lateral size and thin thickness.

[0065] As attached Figure 4 As shown, attached Figure 4 The thermal conductivity diagrams of the boron nitride nanosheet-aramid nanofiber composite films prepared in Examples 3-5 and Comparative Examples are given in FIG. 2+ The highest TC value obtained when the concentration was 4mmol / L was 27.57W·m -1 ·K -1 , and the TC value increases with Ca 2+ The reason for the synchronous growth of concentration may be that the lateral size of BNNS increases, thereby reducing phonon scattering at the boundary; secondly, the microstructure of the resulting film after the composite of ANF and BNNS is denser and the interface interaction is stronger.

[0066] The boron nitride nanosheet-aramid nanofiber composite film and the preparation method thereof of the present invention prepare a high aspect ratio BNNS with large lateral size and small thickness by calcium ion cross-linking sodium alginate assisted ball milling exfoliation, thereby improving the interface phonon scattering between BNNS, making the interface density of the composite material lower and the contact area of ​​the interface larger, thereby improving the thermal conductivity of the composite film; secondly, the ANF and BNNS are effectively compounded by hot pressing, and the BNNS are oriented in-plane to construct a continuous thermal conductive network in the plane, so that the composite material has good thermal conductivity.

[0067] The above embodiment is only one of the implementation methods that can realize the technical solution of the present invention. The scope of protection claimed by the present invention is not limited only to this embodiment, but also includes changes, replacements and other implementation methods that can be easily thought of by any technician familiar with the technical field within the technical scope disclosed by the present invention.

Claims

1. A method for preparing a boron nitride nanosheet-aramid nanofiber composite film, characterized in that: include: Dissolve calcium chloride in sodium alginate aqueous solution to obtain Ca 2+ / SA cross-linking solution; Adding hexagonal boron nitride to Ca 2+ / SA cross-linking solution, pre-wetting is achieved by magnetic stirring to obtain a pre-wetted SA / BNNS solution; The pre-soaked SA / BNNS solution was ball-milled and washed to obtain a BNNS / water suspension; Mixing the BNNS / water suspension with the ANF / DMSO dispersion to obtain a BNNS / ANF mixed solution; The BNNS / ANF mixed solution was vacuum filtered, dried and hot pressed to obtain a boron nitride nanosheet-aramid nanofiber composite film.

2. The method for preparing a boron nitride nanosheet-aramid nanofiber composite film according to claim 1, characterized in that: Ca 2+ Ca / SA cross-linking solution 2+ The concentration is 1-4mmol / L.

3. The method for preparing a boron nitride nanosheet-aramid nanofiber composite film according to claim 1, characterized in that: The pre-soaked SA / BNNS solution was ball-milled and washed to obtain a BNNS / water suspension, and the ball-milling time was 12-24 h.

4. The method for preparing a boron nitride nanosheet-aramid nanofiber composite film according to claim 1, characterized in that: The pre-soaked SA / BNNS solution was ball-milled and washed to obtain a BNNS / water suspension, which was washed with deionized water.

5. The method for preparing a boron nitride nanosheet-aramid nanofiber composite film according to claim 1, characterized in that: The concentration of the BNNS / water suspension was 5-10 mg / mL.

6. The method for preparing a boron nitride nanosheet-aramid nanofiber composite film according to claim 1, characterized in that: The preparation process of ANF / DMSO dispersion is as follows: The para-PPTA fibers and potassium hydroxide were dispersed in DMSO and stirred continuously to obtain an ANF / DMSO dispersion.

7. The method for preparing a boron nitride nanosheet-aramid nanofiber composite film according to claim 1, characterized in that: The concentration of ANF / DMSO dispersion was 1-5 mg / mL.

8. The method for preparing a boron nitride nanosheet-aramid nanofiber composite film according to claim 1, characterized in that: The preparation process of sodium alginate aqueous solution is as follows: Sodium alginate is added into deionized water, and stirred to dissolve to obtain a sodium alginate aqueous solution.

9. A boron nitride nanosheet-aramid nanofiber composite film, characterized in that: The film is prepared by the method for preparing the boron nitride nanosheet-aramid nanofiber composite film as described in any one of claims 1 to 8.

10. The boron nitride nanosheet-aramid nanofiber composite film according to claim 9, characterized in that: The thermal conductivity of the boron nitride nanosheet-aramid nanofiber composite film is 23.86-27.57 W·m -1 ·K -1 .

Citation Information

Patent Citations

  • Method for preparing drug-loading nanocomposite through ball-milling modification of mineral soil and application

    CN103039442A

  • Hydroxyethyl cellulose / boron nitride nano composite film and preparation method thereof

    CN113416334A

  • Boron nitride nanosheet / aramid nanofiber composite film prepared by ball-milling hydroxyethyl cellulose and preparation method of boron nitride nanosheet / aramid nanofiber composite film

    CN117304535A

  • Methods and compositions for sustainable textile materials

    US20240271334A1

Cited By

  • High-thermal-conductivity flexible composite film and preparation method thereof

    CN120590659A